"Enduring Patterns of Loyalist Study: Definitions and Contours". Issue 11 (November 2013) - Chopra, Ruma
Abstract: More than a century ago, loyalist historians established the close relationship between the Atlantic colonies and the British Empire. Far from inevitable or natural, the mainland rebellion signaled a radical break from cherished customs, laws, and liberties. Two overlapping categories of scholarship examine the loyalist experience during the long revolutionary era. The first situates the loyalists alongside the rebels within the framework of the nation and challenges the strength and cohesion of patriots. The second places the loyalists as imperial subjects with legitimate claims to British liberties and recounts the loyalist‐British relationship over the long durée. In the first approach, the loyalists disrupt the conventional narrative of the nation; in the second, they participate in the construction of empire.